1989
DOI: 10.1007/bf00859616
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in recurrent urinary tract infections in childhood

Abstract: One hundred children aged 1.5-19.5 years, with recurrent urinary tract infections, at least one of which was febrile (pyelonephritis, PN), were investigated by means of inulin and para-aminohippurate (PAH) clearance tests for the evaluation of glomerular filtration rate (GFR), effective renal plasma flow, and concentrating and diluting capacities. Renal function data were collated with the clinical history and radiological findings. GFR and PAH clearance were found to be reduced compared with controls. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It has been shown that children who have had one episode of pyelonephritis show a lower glomerular filtration rate than healthy controls, which is in agreement with this study, and the glomerular filtration rate was lower in children with renal scars and recurrent pyelonephritis episodes. 26 27 In these studies renal scars were detected by intravenous urography and therefore they may have been larger than the scars detected in this study by a DMSA scan.…”
Section: Resultsmentioning
confidence: 47%
“…It has been shown that children who have had one episode of pyelonephritis show a lower glomerular filtration rate than healthy controls, which is in agreement with this study, and the glomerular filtration rate was lower in children with renal scars and recurrent pyelonephritis episodes. 26 27 In these studies renal scars were detected by intravenous urography and therefore they may have been larger than the scars detected in this study by a DMSA scan.…”
Section: Resultsmentioning
confidence: 47%
“…Except in children below 3 months of age, in whom the quality of the scintigrams is not always ideal, Jakobsson et al [11,12] consider that a normal DMSA scintigram practically excludes the diagnosis of upper urinary tract infection. Studying inulin and para-aminohippuric acid clearance in children with recurrent pyelonephritis, Berg [13,14] showed that the clearance rate was related to the grade of morphological impairment; when both kidneys were normal, the clearance values were still slightly lower than in the normal control group. However, the normality of the kidneys was estimated on the basis of intravenous urography which, even in the opinion of the author [11], is less sensitive than DMSA scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…GFR was generally reduced in patients with early onset PN and a history of several PN infections. Thus, the authors believed long-term prophylactic antibacterial therapy was indicated in patients with early onset PN, in order to prevent recurrences [28]. The high vulnerability of infant kidneys may partially be due to the fact that recognition and treatment of pyelonephritis is often delayed within the first years of life.…”
Section: Current Clinical Indications For Antibacterial Prophylaxismentioning
confidence: 99%